2016
DOI: 10.1186/s13054-016-1396-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation strategies for intensive care unit patients without acute lung injury or acute respiratory distress syndrome: a systematic review and network meta-analysis

Abstract: BackgroundIt has been shown that the application of a lung-protective mechanical ventilation strategy can improve the prognosis of patients with acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). However, the optimal mechanical ventilation strategy for intensive care unit (ICU) patients without ALI or ARDS is uncertain. Therefore, we performed a network meta-analysis to identify the optimal mechanical ventilation strategy for these patients.MethodsWe searched the Cochrane Central Register o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
1
22
0
1
Order By: Relevance
“…Most notably, IPFR is a used clinical predictor of H7N9 VI's outcome in the present study, though its diagnostic utility is disputed in clinical work. 26 In accordance with the present result, previous studies 27,28 have demonstrated that PFR is a very essential indicator to assess the acute lung injury or acute respiratory distress syndrome of a patient. As known, the oxygen transport is diffusion-limited from the alveolus to the pulmonary capillary in patients with pulmonary diseases (i.e., pulmonary fibrosis).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most notably, IPFR is a used clinical predictor of H7N9 VI's outcome in the present study, though its diagnostic utility is disputed in clinical work. 26 In accordance with the present result, previous studies 27,28 have demonstrated that PFR is a very essential indicator to assess the acute lung injury or acute respiratory distress syndrome of a patient. As known, the oxygen transport is diffusion-limited from the alveolus to the pulmonary capillary in patients with pulmonary diseases (i.e., pulmonary fibrosis).…”
Section: Discussionsupporting
confidence: 91%
“…As known, the oxygen transport is diffusion-limited from the alveolus to the pulmonary capillary in patients with pulmonary diseases (i.e., pulmonary fibrosis). 29 Several reports [26][27][28][29] have shown that the PFR responds to an increase of diversion at a constant oxygen saturation by indicating poorer pulmonary function. Thus, it is reasonable to assume that the PFR may be used in clinical settings as an indicator of predicting pulmonary function status of patients with H7N9 VI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has drawn similar conclusions on the aspects around optimal ventilation [6].…”
mentioning
confidence: 55%
“…A number of interventions have been proposed in the past decade; however, few of them obtained strong recommendation [5,6]. Only lung-protective mechanical ventilation strategy has been proven beneficial for prognosis of these patients [5,7]. Neuromuscular blocking agents (NMBAs) may be a useful therapeutic strategy in patients with ARDS [8].…”
Section: Backgroundsmentioning
confidence: 99%